Atlas of world architecture - Braun, Markus Sebastian; Uffelen, Chris van. (Salenstein, Switzerland : Braun Pub., 2013)
The spirit of an era is reflected by its architecture. The worldwide turbulences of the past years have led to a correspondingly unparalleled diversity of buildings. This compendium presents an international exhibition of contemporary architecture against a backdrop of global trends, local traditions, functional demands, economical constraints and individual styles. The selection includes stunning designs from the most sought-after architects and talented up-and-coming companies, demonstrating new interpretations of forms to suit anticipated future demands. The Atlas of World Architecture sets a benchmark for buildings of all typologies from the past five years that have earned their place in architectural history.
Includes indexes.
Keywords: Architecture, Modern -- 21st century; Architecture, Modern -- 21st century -- Pictorial works